Smaller Pituitary Volumes in Patients with Delusional Disorder - Gurok, Mehmet Gurkan; Keles, Denizhan Danacı; Korkmaz, Sevda; Yildirim, Hanefi; Kilic, Mehmet Çağlar; Atmaca, Murad (NLM (Medline), 2019)
Introduction: Delusional disorder shares some clinical characteristics of OCD and hypochondriasis. Delusions compared to obsessions in the OCD and compared to bodily preoccupations in the hypochondriasis are more established beliefs. Aim: To measure pituitary volumes in patients with delusional disorder and hypothesized that volumes would be reduced in those patients by a mechanism that we could not account for before for patients with OCD and hypochondriasis. Methods: Eighteen patients with delusional disorder and healthy controls were included into the study. Pituitary gland volumes were measured. Results: When using independent t test, the mean total pituitary volume was 777.22±241.28 mm3 in healthy controls, while it was 532.11±125.65 mm3 in patients with delusional disorder. The differences in regard to pituitary gland volumes between patients with delusional disorder and healthy control subjects were statistically meaningful (p<0.01), as supported by ANCOVA, with the covariates of age, gender and total brain volumes as covariates. Conclusion: We determined that patients with delusional disorder had smaller pituitary volumes compared to those of healthy control subjects. © 2019 Mehmet Gurkan Gurok, Denizhan Danaci Keles, Sevda Korkmaz, Hanefi Yildirim, Mehmet Caglar Kilic, Murad Atmaca.
Keywords: delusional disorder; Pituitary; smaller; volumes